2019
DOI: 10.1098/rsif.2018.0738
|View full text |Cite
|
Sign up to set email alerts
|

The role of adhesion in contact mechanics

Abstract: Adhesive (e.g. van der Waals) forces were not generally taken into account in contact mechanics until 1971, when Johnson, Kendall and Roberts (JKR) generalized Hertz’ solution for an elastic sphere using an energetic argument which we now recognize to be analogous to that used in linear elastic fracture mechanics. A significant result is that the load–displacement relation exhibits instabilities in which approaching bodies ‘jump in’ to contact, whereas separated bodies ‘jump out’ at a tensile ‘pull-off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(73 citation statements)
references
References 129 publications
(245 reference statements)
2
59
0
2
Order By: Relevance
“…Among them, the lack of a universal mechanism for taking into consideration different factors, in particular, the properties of materials in the intermediate layers between the bodies in contact. Studies [17][18][19] address the models of properties of the rough surfaces of contacting bodies, taking into consideration their wave-like shapes. Papers [20][21][22] describe the effect of a geometric shape of surfaces and the distribution of a material's properties on the contact interaction between elastic bodies.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Among them, the lack of a universal mechanism for taking into consideration different factors, in particular, the properties of materials in the intermediate layers between the bodies in contact. Studies [17][18][19] address the models of properties of the rough surfaces of contacting bodies, taking into consideration their wave-like shapes. Papers [20][21][22] describe the effect of a geometric shape of surfaces and the distribution of a material's properties on the contact interaction between elastic bodies.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Contact mechanics with adhesion of elastic bodies has been applied to cell adhesion, originally in the form of the simple Johnson-Kendall-Roberts (JKR) theory [1], where it was shown that, unless it is disrupted, the cytoskeleton provides cells with a three-dimensional structure that is appropriate for JKR theory to be valid [2]; this includes that the material is relatively soft for the contact size to be regulated by what is essentially a Griffith energy criterion (for a recent review of adhesion, see [3]).…”
Section: Introductionmentioning
confidence: 99%
“…10a,b shows the plots of the relative contact areaà = π 1 − e 2ã2 versus the dimensional measure of stretch in the strain-and stress-controlled cases, respectively. (v) Axisymmetric loadingRecall[3] that the JKR-type models of adhesion are applicable for relatively large values of the Tabor parameter[39] μ T = RGwhere z 0 is the range of attraction of adhesive forces.…”
mentioning
confidence: 99%
“…In a recent paper [1], the role of adhesion in contact mechanics has been reviewed starting in particular from the fundamental contribution of Johnson, Kendall and Roberts (JKR) [2], who generalized Hertz' theory to include van der Waals forces described as infinitely short range forces, so that a "contact area" can still be defined, which includes both compressive and tensile stresses. JKR theory has been confirmed in a number of investigations: in principle it should hold only for soft materials and large sphere radius, but in practice for a single, smooth asperity, it holds approximately even for dimensions appropriate to the Atomic Force Microscope (AFM), or the Surface Force Apparatus (SFA).…”
Section: Introductionmentioning
confidence: 99%